526. Antimicrobial Selection Based on Precision Metagenomics Compared with Standard Urine Culture/Susceptibility: A Reliability and Inter-rater Agreement Analysis for Application in Patients with Urinary Tract Infections. (15th December 2022) - Hanson, Amy P; Stinnett, Rita C; Bhasin, Ajay; Conrad, Heather; Nguyen, David C; Ramchandar, Nanda; Boswell, Malcolm; Stauffer, Stacie; Farnaes, Lauge; Briggs, Benjamin; Briggs, Benjamin; Schlaberg, Robert
Abstract: Background: Management of urinary tract infections (UTIs) is highly variable and ∼50% of affected women may receive inappropriate antimicrobials. Precision Metagenomics-based detection of pathogens and antimicrobial resistance (AMR) markers can inform antimicrobial selection in support of stewardship practices. We investigated inter-physician agreement of culture and metagenomic results in a retrospective analysis. Methods: We used de-identified urine samples with results of urine culture & antimicrobial susceptibility testing (AST, n=25, 76% culture-positive) and the Explify® Urinary Pathogen ID/AMR Panel (UPIP, IDbyDNA Inc). UPIP is a Precision Metagenomics method to detect >170 uropathogens and >2, 000 AMR markers. Four physicians reviewed culture/AST and UPIP results independently to assess if and how they would treat based on each set of results in a middle-aged, female patient with uncomplicated UTI (no comorbidities or medication allergies). Consensus was defined by simple majority; treatment decisions and antimicrobial choice were adjudicated by an infectious disease trained pharmacist. Inter-rater agreement (Fleiss' kappa) and reliability for accurate case management (reference: adjudicator) were estimated for each method. Results: Analytical agreement for uropathogen identification between the two methods was 72% with 95% positive agreement for common uropathogens. Consensus on whether or not to treat was reached for 96% (24/25) of cases for both culture/AST and UPIP; decisions were concordant between methods for 88% of cases (22/25). Inter-rater agreement was high (culture: k=0.73, UPIP: k=0.68; p< 0.05). Physicians were more likely to decide to treat based on culture results (17/25, 68%) than UPIP (15/25, 60%). UPIP detected additional organism(s) and/or AMR marker(s) compared with culture/AST alone that were informative for stewardship-guided treatment decisions in 28% (7/25) of samples. Figure 1: Physician Consensus Treatment Decisions Based on Results of Urine Sample Analysis by Precision Metagenomics or Urine Culture/AST Four infectious disease physicians independently reviewed paired results from analysis of a set of 25 clinical remnant urine samples by an investigational Precision Metagenomics method (UPIP) and by standard urine culture/AST and determined whether or not treatment would be warranted. Figure 2: Summary of Changes in Antimicrobial Selection based on Interpretation of Precision Metagenomics vs Culture/AST Results An infectious disease pharmacist reviewed and adjudicated hypothetical antimicrobial selections. All antimicrobial selections based on the results of the Precision Metagenomics method (UPIP) were found to be appropriate; in 7/15 cases, hypothetical treatment based on UPIP results would have resulted in a change in management that was evaluated to be consistent with stewardship practices. Conclusion: Physician agreement on hypothetical treatment recommendations was comparable between the investigational method (UPIP) and the reference method (urine culture/AST). In no case was there inappropriate consensus to treat based on UPIP results alone. The findings from this pilot analysis support the feasibility of metagenomics-guided management of UTIs. Disclosures: Benjamin Briggs, MD, PhD, CloudCath: Advisor/Consultant|CosmosID: Employee Benjamin Briggs, MD, PhD, CloudCath: Advisor/Consultant|CosmosID: Employee Robert Schlaberg, MD, MPH, IDBYDNA INC: Board Member|IDBYDNA INC: Explify-related IP|IDBYDNA INC: Employee|IDBYDNA INC: Stocks/Bonds.